Disclosure Responses to a Corruption Scandal: The Case of Siemens AG - Blanc, Renata (Journal of business ethics, 2019)
In the current study, we examine the changes in disclosure practices on compliance and the fight against corruption at Siemens AG, a large German multinational corporation, over the period 2000–2011 during which a major corruption scandal was revealed. More specifically, we conduct a content analysis of the company’s annual reports and sustainability reports during that period to investigate the changes of Siemens’ corruption and compliance disclosure using both quantitative and qualitative methods. Through the lens of legitimacy theory, stakeholder analysis, and organizational façades, we find evidence that Siemens changed its compliance and corruption disclosure practices to repair its legitimacy in the wake of the 2006 corruption scandal. We analyze these strategies more closely by using the rational, progressive, and reputation façades framework (Abrahamson and Baumard in The Oxford Handbook of Organizational Decision Making, pp 437–452, 2008). Our primary findings suggest that the annual reports show peaks of disclosure amounts on corruption and compliance disclosures earlier than sustainability reports, which can be partly explained by analyzing the disclosures made about—and to—the different stakeholder groups. We find that the annual report focuses more on internal stakeholders such as employees, while the sustainability report focuses more on external stakeholders such as suppliers. We also find that the company uses the façades differently depending on which report is being analyzed.